AB1415-HPR PATIENTS PERSPECTIVES ON SELF-MANAGEMENT OF AXIAL SPONDYLOARTHRITIS FATIGUE. (June 2019) - Tziatzou, Ntoriana; Borg, Andrew; Mercieca, Cecilia; Ryan, Sarah
Abstract : Background: Axial spondyloathritis (ax-SpA) is a chronic inflammatory arthritis that mainly affects the axial skeleton and can lead to bony ankyloses. Pain, stiffness and fatigue are the most frequently ax-SpA-reported symptoms. Ax-SpA fatigue is multidimensional incorporating physical, psychological and social components, implying that self-management strategies are crucial. Objectives: This study aimed to explore the self-management of ax-SpA fatigue. Patients perceptions of whether clinicians give importance to ax-SpA fatigue were also explored. Methods: A qualitative phenomenological approach was used. A purposive sample of 10 patients with ax-SpA, who were experiencing fatigue (≥7cm on a 10cm VAS scale and attending a specialist rheumatology clinic were selected. The participants completed a demographic questionnaire, the Bath ankylosing spondylitis disease activity index (BASDAI) and the Bath ankylosing spondylitis functional index (BASFI) outcome measures. Data was collected using semi-structured interviews that lasted about 30-60 minutes. Open-ended questions such as How do you manage fatigue?, How well do you think you are coping with fatigue?, What can be done to help address fatigue? and Is fatigue usually discussed when you attend clinic? were asked to the participants. Interviews were tape-recorded, transcribed verbatim and analysed using Colaizzis framework. Two independent reviewers and five participants reviewed the data. Results: Ten ax-SpA patients (5 males) with a mean age of 46.6 years (29 - 69) participated in the study. The mean BASDAI was 5.4 and mean BASFI was 5. Most of the participants had disease duration of longer than 5 years. Learning to self-manage fatigue was clearly a difficult process for the participants. Only four participants felt that they had learnt to cope with fatigue. They described how they overcame the initial feelings of anger and denial to cope with the fatigue and being told fatigue was part of the condition was helping in accepting the fatigue. There was consensus that fatigue was not addressed in the clinical setting. Participants felt that they were not guided and supported enough to manage fatigue. More information was needed from health care professionals (HCP) on fatigue management. There was a feeling that HCP focused on the management of pain rather than fatigue. Conclusion: This research highlighted a clear lack of knowledge about self-management skills to manage ax-SpA fatigue. Lack of adjustments and coping with fatigue was prominent even in patients who had long disease duration. Furthermore, fatigue was not addressed in clinical practice. Understanding patients beliefs is an important step towards guiding them to self-manage fatigue. Patients should be guided in implementing self-management plans that would fit their goals, priorities and lifestyle. Self-management is important in improving health outcomes and quality of life. Disclosure of Interests: None declared